Effect of Competition in Rape SeedPlants at Growing Stages Periods - الشماع, ليث (Iraqi Journal of Science, 2025)
A field trial was conducted at Abu-Ghraib research station, Baghdad , Iraq ,The objectives were to study the effect of the competition with in plants on period long of growth stages by the effects nitrogen fertilizer and planting space of rape seed . A split-plot in a randomized complete of block design with three replications were used . Five levels of nitrogen fertilizer ( 120,160,200,240,280 Kg / ha ) were assigned to main plots, whereas planting space(30,40 and 50cm) in sub-plots .The result obtained confirmed that the plant did not varied significantly at the first three growing stages (A no real leaves only the 2 cotyledons can be seen),B1 (one real leaf is spread and unfurled),B4 (four real leaves is spread and unfurled ) and stage C1-C2 (vegetation starts again young leaves appear- space between the knots is visible the stem appears) by different plant densities and nitrogen fertilizer. The plants at high plant density 30 cm gaves the higher number of days to 50% D1( the stuck buds are still hidden by the terminal leaves) and stage E (elongation of side-stems) .The plant at 40 cm plant density gaves the higher number of days to F1 (the first flowers open) ,F2 (elongation of the stem, many flowers are open) and stage G4 (the first ten pods are uneven and lower number of days to stage D2( the main inflorescence sticks out the buds are still stuck to one anther the secondary inflorescence are visible the stem is higher than 20cm (20cm between the flowers and the bottom of the rosette) and G1 (the first petals fall down the first ten pods are not longer than 2cm the flowering of secondary inflorescence begins at this stage) . However, the low plant density 50 cm gaves the higher number of days to D2 and G1 stages and lower number of days to B4,D1,E,F1,F2 and G4 stages . The plants at level 120 Kg N/ ha gaves the higher number of days to 50% D1 stage and lower number of days to G1 stage and no significant with level 160 Kg N/ ha to gaves the higher number of days to F1 stage ,The plants at level 200 Kg N/ ha gaves the higher number of days to D2 stage and lower number of days to D1and F1 stages at level 280 Kg N/ha . The Interaction between plant density 30cm and nitrogen fertilizer 120 and 160 Kg N/ha gaves the higher number of days to (B8 eight leaves are spread and unfurled ,D1, G4) and F1 stages respectively ,The plants density 40 cm gaves the higher number of days to F2 stages at levels 120,200,240,280 Kg N/ ha and at lest tow levels at G4 stage ,So the lower plant density 50 cm gaves the higher number of days to G1 at levels 120 and 280 Kg N/ha and level 240 Kg N/ha at D2 stage .